Isolation and characterization of endophytic fungi from Acacia mangium / Muhammad Haris Hussin - Hussin, Muhammad Haris (2019)
Acacia mangium is the most common plantation tree species that are widely planted mainly in Malaysia, Vietnam, Indonesia, Philippines and Thailand. Endophytic fungi are essential microorganism that are presents within the plants tissues, including a broad range of plants in various ecosystems, and thus play an essential role in the natural environment. There are more than one million species of endophytes and are estimated to exist based on a ratio of vascular plants to fungal species of 1:4 or 1:5. Furthermore, the study of the endophytic fungi from the Acacia mangium might deliver a new knowledge and understanding. The project will be helpful to identify which endophytic fungi associated with the plant. Therefore, the purpose of the research are to isolate endophytic and identify the endophytic fungi from Acacia mangium by using the morphological characteristics. Based on the result obtained, all the endophytic fungi observed under the light microscope were conidia and the division of endophytic fungi were Ascomycota except AM20 is in categorized as Zygomycota. It can be concluded that most of the fungi isolated were belonged to Ascomycota consist of septate hyphae and some were belonged to Zygomycota which consist of aseptate hyphae and it is recommended for future researcher to study about endophytic fungi because of its important and gain new knowledge and understanding.